Developmental outcomes in adolescence of children with autism spectrum disorder without intellectual disability: A systematic review of prospective studies. (July 2021) - Rosello, Rocio; Martinez-Raga, Jose; Mira, Alvaro; Girela, Braulio; Cortese, Samuele
Highlights: Diagnosis of ASD-without ID and severity of symptoms were highly stable over time. EF and ToM improved in adolescence, although deficits remained compared to TD. Psychiatric comorbidity in ASD children without ID was relatively stable over time. Abstract: Individuals with Autism Spectrum Disorder (ASD) without intellectual disability (ID) represent approximately two-thirds of the ASD population. Here we focused on prospective research assessing different areas of functioning of children with ASD, without ID, until adolescence. Based on a pre-registered protocol (PROSPERO CRD42020189029), a systematic review of prospective studies (published between 01.01.2010 and 01.01.2020) was conducted. Twenty-eight studies met eligibility criteria. Findings indicated that ASD diagnosis and the Intelligence Quotient were highly stable over time across studies. Executive Functioning, Theory of Mind and Central Coherence processes tended to improve, although deficits remained when compared to typically developed controls. Adaptive difficulties and psychiatric comorbidity were relatively stable over time. We discuss potential implications of the findings for clinicians and educators and suggest recommendations for future research.